2011
DOI: 10.1007/s11325-011-0578-x
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of the Croatian version of the Epworth sleepiness scale and STOP questionnaire as screening tools for obstructive sleep apnea syndrome

Abstract: Both ESS and STOP questionnaires successfully distinguished healthy subjects from subjects with OSAS. The STOP questionnaire had better probability to correctly predict high-risk patients for OSAS compared to ESS. We propose that the STOP questionnaire could be used as an easy-to-use and accurate screening tool in identification of patients with risk for OSAS in the general population, but it has not been tested in the Croatian population yet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…Other studies conducted on patients referred to a sleep clinic include one study on an Asian population which found a sensitivity of 84.7 %, specificity of 52.6 %, PPV of 84.4 %, and NPV of 53.2 % against AHI>5 [13]. An evaluation of the Croatian version of STOP questionnaire using a cutoff value of 2 in the screening tool showed sensitivity of 96 %, specificity of 83 %, PPV of 61 %, and NPV of 95 % against AHI>5 [15]. Another study involving high-risk patients found a sensitivity of 93.8 %, specificity of 33.3 %, PPV of 75 %, and NPV of 71.4 % against AHI>5 [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies conducted on patients referred to a sleep clinic include one study on an Asian population which found a sensitivity of 84.7 %, specificity of 52.6 %, PPV of 84.4 %, and NPV of 53.2 % against AHI>5 [13]. An evaluation of the Croatian version of STOP questionnaire using a cutoff value of 2 in the screening tool showed sensitivity of 96 %, specificity of 83 %, PPV of 61 %, and NPV of 95 % against AHI>5 [15]. Another study involving high-risk patients found a sensitivity of 93.8 %, specificity of 33.3 %, PPV of 75 %, and NPV of 71.4 % against AHI>5 [14].…”
Section: Discussionmentioning
confidence: 99%
“…Vana and colleagues [14] concluded in their study that STOP-Bang could identify more patients with OSA than ESS in a sleep clinic setting with a sensitivity of 94.7 % compared to a sensitivity of 26.3 % in ESS. Another study by Pecotic and others showed that STOP-Bang had better probability to correctly predict high-risk patients for OSA compared to ESS [15]. To our knowledge, however, there is no study examining the utility and diagnostic accuracy of the Arabic version of the STOPBang questionnaire.…”
mentioning
confidence: 91%
“…Epworth Sleepiness Scale which is validated in Croatian was used to asses sleepiness during routine daily activities 55 . The questionnaire is formed out of 8 statements which describe everyday activities (sitting and reading, watching TV, sitting at a meeting while not actively participating in it, being in a car for more than an hour as a passenger, sitting after a meal whitout alcoholic beverage, sitting and talking to someone, sitting in the car in a traffic jam for a few minutes, lying and relaxing in the living room).…”
Section: Epworth Sleepiness Scalementioning
confidence: 99%
“…Normal values are between 0 and 6, 7 and 8 indicate moderate level of daytime sleepiness, while 9 to 24 high level of daytime sleepiness. Patients with high level of daytime sleepiness should undergo further evaluations 55 .…”
Section: Epworth Sleepiness Scalementioning
confidence: 99%
“…Sleep studies lasting less than 4 h were not accepted, and in such cases, a second recording was undertaken. The self-administrated questionnaire, the Epworth Sleepiness Scale (ESS), validated in Croatian language by our group [26] was used to measure excessive daytime sleepiness.…”
Section: Sleep Assessmentmentioning
confidence: 99%